Student’s Attitude An Anxiety on Listening Class (A Descriptive Quantitative Study of Second Semester English Education Students’ of Uin Fatmawati Sukarno Bengkulu) - Endang Haryanto; Febri Aini Adalta (JELP Journal of English Language and Pedagogy, 2022)
This study aims to determine the form of attitudes and anxiety, and level of anxiety that experienced by students in the listening class on students’ of English Study Program at UIN Fatmawati Sukarno Bengkulu. This study uses a descriptive method with a quantitative approach of survey type. The sample in this study was the second semester students’ of English education with a total of 47 students’. The research data was taken using a questionnaire with a total of 28 items related to attitudes and anxiety. The attitude questionnaire was divided into 2 categories, positive and negative. The result of data analysis in positive statements, the average score is 3.61 (72.1%). Likewise with negative statements, the average score is 3.48 (70%). For students’ anxiety levels, based on the results of data analysis, 29 students (62%) categorized into "relaxed" and 13 students’ (28%) are "very relaxed", and only 5 students (11%) belong to the moderate level of anxiety with the predicate "Midly Anxious". Based on these results, it can be concluded that the attitude students on the listening class is positive and students level of anxiety are tend to be low and the type of students anxiety are debilitative or positive.